Answer :

(i) We use


(x + 2z)(2x + z) =


(x + 2z)(2x + z) =


(ii) 4(x + 2y)(2x + y) = (2x + 4y)(4x + 2y)


We use


4(x + 2y)(2x + y) =


4(x + 2y)(2x + y) = ( 3x + 3y)2-(2y – 2x)2


(iii) We use


(x + 98)(x + 102) =


(x + 98)(x + 102) = (x + 100)2-(x-100)2


(iv) 505 × 495 = (500 + 5)(500-5)


We use (a + b)(a - b) = a2 - b2


505 × 495 = 5002-52


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the product:Karnataka Board - Mathematics Part I

If a, b are ratioKarnataka Board - Mathematics Part I

Use the identity Karnataka Board - Mathematics Part I

Express the folloKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Simplify:

Karnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Evaluate these usKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I